Deadlock in sustainable aviation fuels: A multi-case analysis of agency. (May 2021) - Dodd, Tracey; Yengin, Duygu
Highlights: Policy makers, airlines, and jet fuel companies perceptions are analyzed. Data show a deadlock that hinders deployment of renewable jet fuels. Greater within-sector accountability and collective leadership is required. Abstract: Scholars, policymakers, and airlines have known for decades that aviation must decarbonize to combat climate change. The most obvious short-term solution is to replace fossil fuels with sustainable aviation fuels. Yet little progress has been made because airlines, policymakers, and fuel companies are caught in a deadlock over how to move forward. With the literature largely silent, we interviewed 36 senior executives with influence over the transition and triangulated their opinions against archival data. Our analysis reveals free-riding across sectors, insufficient investment, and a reticence by anyone to lead the charge. We argue that these issues could be overcome through collective leadership rather than a few champion entities willing to invest. Our findings advance collective action theory by uncovering and analyzing "free-riding across sectors", offering possible strategies that could address the issue by showing how the current deadlock between airlines, policymakers, and fuel companies could be overcome.